ANALISIS KETERSEDIAAN SARANA DAN PRASARANA PADA LINGKUNGAN PERMUKIMAN - Massikki, Muhammad Najib (MEKTEK, 2005)
Settlement is the place where human being spent their lives. Its’ environment should be balanced with natural environment together with dweller. Settlement infrastructure is the basic needs besides of food and cloths and its the most important thing dweller. The aim of this study is how to ge detail information through the analysis of settlement infrastructure particularly in the slum areas of down town. Local theory based on the environmental condition of Pasar Masomba and surroundings which is place in the Tatura Utara where lying in Palu river banks. The result of this study showed that some infrastructure i.e., health, education, public area space, roads, and waste are needed